2019
DOI: 10.1177/1120672119850076
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival tattoo with inadvertent ocular globe penetration and vitreous involvement: Clinico-pathological correlation and scanning electron microscopy X-ray microanalysis

Abstract: Purpose: The aim is to report a case of conjunctival tattooing with inadvertent injection of tattoo ink into the vitreous cavity and its consequences, the scanning electron microscopy X-ray microanalysis of the ink components, and the microscopic findings of the affected conjunctiva and vitreous. Methods: Descriptive case report. Results: A 32-year-old man complained of ocular pain and blurred vision after undergoing a subconjuctival red ink tattoo in his left eye. Ophthalmologic examination revealed best corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Traditional tattoo inks, when inadvertently injected inside the anterior chamber or vitreous, can cause devastating injury to the eye and its structures including uveitis, corneal endothelial failure, secondary glaucoma, retinal detachments, infection, and loss of eye. 9 , 11 , 13 , 14 , 15 , 17 , 18 , 19 From our literature review, 10/14 (71%) cases previously reported were complicated by inadvertent globe puncture, and these cases had more serious visual consequences, especially if ink was injected while inside the eye. In cases without globe puncture, less serious side effects tend to occur and are likely related to hypersensitivity of the conjunctiva to the ink itself and include irritation and conjunctival chemosis as in our cases and others, as well as episcleral nodules.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Traditional tattoo inks, when inadvertently injected inside the anterior chamber or vitreous, can cause devastating injury to the eye and its structures including uveitis, corneal endothelial failure, secondary glaucoma, retinal detachments, infection, and loss of eye. 9 , 11 , 13 , 14 , 15 , 17 , 18 , 19 From our literature review, 10/14 (71%) cases previously reported were complicated by inadvertent globe puncture, and these cases had more serious visual consequences, especially if ink was injected while inside the eye. In cases without globe puncture, less serious side effects tend to occur and are likely related to hypersensitivity of the conjunctiva to the ink itself and include irritation and conjunctival chemosis as in our cases and others, as well as episcleral nodules.…”
Section: Discussionmentioning
confidence: 88%
“…26 Although there have already been reports of immediate anterior uveitis after scleral tattooing, there have been no reports of an uncomplicated scleral tattooing presenting with delayed tattoo-associated uveitis so it is unknown whether the proximity of the ink may increase this risk. 13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rodríguez-Avila и соавт. сообщили о случае проникновения пигмента в строму роговицы, при этом острота зрения в описанном случае была сохранена только благодаря тому, что пигмент остался в зоне средней периферии и не затронул центр роговицы [14].…”
unclassified